2012
DOI: 10.1118/1.3675972
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the spatial resolution of an online dose verification device

Abstract: The LSF for a new novel online detector has been measured at 6 MV using a narrow slit technique, and this measurement has been validated by Monte Carlo simulation. The detector response function derived from line spread function has been applied to recover measured IMRT fields. The results have shown that the device measures IMRT fields accurately within acceptable tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…suggests that a 5 mm resolution (at an isocenter) is sufficient to detect errors in IMRT delivery. Also, Asuni et al . reported the spatial resolution of the COMPASS transmission detector using narrow slit fields.…”
Section: Discussionmentioning
confidence: 99%
“…suggests that a 5 mm resolution (at an isocenter) is sufficient to detect errors in IMRT delivery. Also, Asuni et al . reported the spatial resolution of the COMPASS transmission detector using narrow slit fields.…”
Section: Discussionmentioning
confidence: 99%
“…Some approaches lead to detailed checklists, but research has shown that a risk of “checklist fatigue” occurs when such lists grow to be too long, thus, defeating their primary purpose . Other groups have chosen to focus their efforts on the development of automated approaches, using software and/or hardware, to automatically identify potentially dangerous discrepancies . Some software approaches evaluate plan quality to ensure that planners did not inadvertently fail to achieve important quality metrics .…”
Section: Introductionmentioning
confidence: 99%
“…Estas metodologias foram escolhidas para este trabalho por ambas dependerem da Função de Espalhamento Pontual (do inglês Point Spread Function -PSF). A PSF, que é uma função de resposta do sistema a um estímulo pontual, é amplamente utilizada em análises de resolução espacial de vários sistemas, inclusive nos de diagnóstico [3][4][5][6][7][8] .…”
Section: Introductionunclassified